PELAKSANAAN FUNGSI KELUARGA OLEH PEREMPUAN DISABILITAS SINGLE PARENT - Namira Cita Suyanto; Rina Susanti (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
Research on the Implementation of Family Functions by Single-Parent Disabled Women in Pekanbaru was conducted to explain the lives of single-parent disabled women in interacting in their environment and to find out the implementation of family functions by single-parent disabled women. The family functions are carried out in the family to create a harmonious ideal family. The method used in this research was qualitative research and there were three informants: single-parent women with physical disabilities. This study discusses 6 family functions carried out by single-parent disabled women: socialization, affection, education, religion, protection, and economic functions. The results obtained from the study are single-parent women with disabilities have daily lives by interacting with the surrounding environment and carrying out family functions. However, several family functions are not carried out optimally by single-parent disabled women. This is because of some obstacles they have in their daily lives.